A distributed implementation of the extended schematic protection model - Ammann, P.; Sandhu, R.S.; Suri, G.S. (Computer Security Applications, 7th Annual Conference, 1991)
Protection models provide a formalism for specifying control over access to information and other resources in a multi-user computer system. One such model, the extended schematic protection model (ESPM) has expressive power equivalent to the monotonic access matrix model of Harrison, Ruzzo, and Ullman (1976). Yet ESPM retains tractable safety analysis for many cases of practical interest. Thus ESPM is a very general model, and it is of interest whether ESPM can be implemented in a reasonable manner. The authors outline a distributed implementation for ESPM. The implementation is capability-based, with an architecture where servers act as mediators to all subject and object access. Capabilities are made nontransferable by burying the identity of subjects in them, and unforgeable by using a public key encryption algorithm. Timestamps and public keys are used as mechanisms for revocation.< >